Implementasi Pendidikan Karakter Melalui Kegiatan Pramuka Pada Anak Kelas Atas Di SD 3 Tenggeles Mejobo Kudus - Rahayuningrum, Farikha; , Drs. Saring Marsudi, SH. M.Pd (2017)
This purpose of this research was 1) Penelitian ini bertujuan untuk 1) know the characters within the boyscout activity in high class Tenggeles Mejobo Kudus elementary school 3, 2) to describe the obstacle appears on the implementatino of character education through boyscout activity in high class Tenggeles Mejobo Kudus elementary school 3, 3) to describe the solution for the obstacle appears on the implementatino of character education through boyscout activity in high class Tenggeles Mejobo Kudus elementary school 3. This research was qualitative research and descriptive design. The informant of this research was the principle of Tenggeles Mejobo Kudus elementary school 3 and the boyscout coach of Tenggeles Mejobo Kudus elementary school 3 and the boyscout of Tenggeles Mejobo Kudus elementary school 3. The resul of this study was 1) the boyscout activity consists of the character achievement related to PBB (baris berbaris) where the students learn to be agile, discipline, hard work and responsible. tali temali activity, the character achievent on curious, hard work, and responsible. Semafor activity, the character achievement on discipline, responsible, and creative. Indonesia Raya and Boyscout Hymne Singing activity, the character achievement on how to learn to love the mother earth, how to love nature, and appreciate others. 2) on the obstacle related to the implementation of character education through boyscout activity such as the personal factor, the infrastructure and the capital. 3) the solution for those obstacles related coming from the coach, the education department and the parents.